New optical solitons of perturbed nonlinear Schrodinger-Hirota equation with spatio-temporal dispersion - Akinyemi, Lanre; Rezazadeh, Hadi; Shi, Qiu-Hong; İnç, Mustafa; Khater, Mostafa M. A.; Ahmad, Hijaz; Akbar, M. Ali (Elsevier, 2021)
The perturbed nonlinear Schrodinger-Hirota equation with spatio-temporal dispersion (PNSHE-STD) which governs the propagation of dispersive pulses in optical fibers, is investigated in this study using an improved Sardar sub-equation method. The Kerr and power laws of nonlinearity are taken into account. As a result of this improved technique, many constraint conditions required for the existence of soliton solutions emerge. We retrieved several solutions such as the bright solitons, dark solitons, singular solitons, mixed bright-dark solitons, singular-bright combo solitons, periodic, and other solutions. Furthermore, we demonstrate the dynamical behaviors and physical significance of these solutions by using different parameter values.
Keywords: Optical solitons; Improved Sardar sub-equation method; Kerr and power laws; Perturbed nonlinear Schrodinger-Hirota equation